2012
DOI: 10.1159/000343040
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the IgE and IgG4 Sequential Epitopes of Ovomucoid with a Peptide Microarray Immunoassay

Abstract: Background: Ovomucoid (Gal d 1) has been demonstrated to be the most important allergen in IgE-mediated egg allergy. Peptide microarray analysis is a novel method that can provide useful information on the nature of specific allergens. Methods: A peptide microarray immunoassay was performed using a 15- and 20-amino acid (aa) library of overlapping peptides (3-offset) of the primary sequence of ovomucoid. Sera from 50 patients with IgE-mediated egg allergy and reactivity to ovomucoid, with more than 1 year of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 64 publications
6
38
0
Order By: Relevance
“…These observations indicated that the presence of sequential epitope-specific serum IgE antibodies represents the basis of a screening method for persistent egg allergy. In a recent study using microarray techniques, two major Bcell epitopes (AA4e20 and AA46e59) that coincided with the epitopes described previously were identified, 37 indicating that AA4e20 and AA46e59 are clinically relevant epitopes. Although AA4e20 and AA46e59 were recognized by 24% and 32% of patients who tested positive for OM-specific IgE, one third of the patients did not recognize any linear epitopes of OM.…”
Section: Chicken Eggsupporting
confidence: 55%
See 1 more Smart Citation
“…These observations indicated that the presence of sequential epitope-specific serum IgE antibodies represents the basis of a screening method for persistent egg allergy. In a recent study using microarray techniques, two major Bcell epitopes (AA4e20 and AA46e59) that coincided with the epitopes described previously were identified, 37 indicating that AA4e20 and AA46e59 are clinically relevant epitopes. Although AA4e20 and AA46e59 were recognized by 24% and 32% of patients who tested positive for OM-specific IgE, one third of the patients did not recognize any linear epitopes of OM.…”
Section: Chicken Eggsupporting
confidence: 55%
“…Although AA4e20 and AA46e59 were recognized by 24% and 32% of patients who tested positive for OM-specific IgE, one third of the patients did not recognize any linear epitopes of OM. 37 The 3-D conformation of OM, including carbohydrate modifications, is preferentially recognized by IgE in egg allergy patients. Thus, the detection of conformational epitopes is also of importance for the diagnosis and prognosis of egg OM allergy.…”
Section: Chicken Eggmentioning
confidence: 99%
“…Because of these obvious limitations, peptide microarrays have recently been developed and used for allergen epitope identification, like in other fields of nucleic acid [32], protein/allergen [33] and peptide [34] research. Selected examples of published microarrays with synthetic overlapping peptides for human IgE epitope mapping of food allergens were on milk lactoglobulin and casein subunits [20,35], egg ovomucoid [36], peanut and walnut allergens [37,38], including Ara h 1 [37], shrimp allergens [39] and Atlantic salmon and cod parvalbumins [40,41]. Most of the published and above-cited microarray-based analysis of linear IgE epitopes of food allergens is based on 1 previous microarray development for milk allergens [20].…”
Section: Discussionmentioning
confidence: 99%
“…OVM has several unique characteristics, such as stability against heat and digestion by proteinases. There have been a few studies on the IgE-binding epitopes in OVM [7][8][9][10][11] , and the reported binding sites resemble each other ( table 2 ) [12] .…”
Section: Allergenic Components Of Egg Whitementioning
confidence: 95%